Al2O3-modified Ti–Mn–O nanocomposite coated with nitrogen-doped carbon as anode material for high power lithium-ion battery. Issue 47 (25th April 2016) - Bai, Xue; Li, Tao; Zhao, Xin-Yi; Shen, Dong; Lun, Ning; Qi, Yong-Xin; Bai, Yu-Jun
Abstract : Al2 O3 -modified Ti–Mn–O nanocomposite coated with nitrogen-doped carbon using simple method exhibits remarkable rate performance. Abstract : Al2 O3 -modified Ti–Mn–O nanocomposite with nitrogen-doped carbon coating is fabricated using metal chlorides as precursors and acrylonitrile as carbon source. The composite acting as anode material for lithium-ion batteries exhibits a reversible capacity of 420.7 mA h g −1 after cycling 100 times at a current density of 100 mA g −1 and excellent rate capabilities. The enhanced electrochemical performance results from synergistic compositing effect of TiO2 and MnO/MnTiO3 with a small amount of Al2 O3, combining the high capacities of MnO/MnTiO3, the structural stability of TiO2 with the dispersion effect and buffer function of Al2 O3 .